KENYAMANAN BALE METEN RUMAH TRADISIONAL DITINJAU DARI SUDUT ERGONOMIS DI DESA ADAT BATUAN SUKAWATI GIANYAR BALI - Sudarmanto, I Gede; Mahayana, I Made Bulda; Jirna, I Nyoman (Poltekkes Kemenkes Denpasar, 2024)
Abstract. Residential houses have forms and functions to protect humans from natural influences. A good house must meet several requirements such as; environmental planning, spatial planning, building planning and utilities. Traditional Balinese architecture basically combines two main human needs, namely